DAMPAK KECERDASAN EMOSI REMAJA DAN RESPON IKLAN DI MEDIA SOSIAL TERHADAP PENERAPAN PRINSIP EKONOMI KEGIATAN KONSUMSI SISWA KELAS XI IPS DI SMA NEGERI 1 KEPANJEN - Evan Gyovani; Agung Haryono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
Human is faced towards various decisions in terms of consumption. Deciding on consumption activities needs guidance, therefore the decisions could become more rational to do. Nowadays, the majority of students can access social media on their cell phones to consume any products, however this condition shifts from what they need to what they desire or want. The majority of students are lack of careful consideration in consuming products. Based on the problem above, it is necessary to conduct research on the application of economic principles of consumption activities in students of class XI IPS in SMA Negeri 1 Kepanjen.DOI: https://dx.doi.org/10.17977/UM014v11i12018p0029